PeSA 2.0: A software tool for peptide specificity analysis implementing positive and negative motifs and motif-based peptide scoring. (December 2022) - Topcu, Emine; Ridgeway, Nashira H.; Biggar, Kyle K.
Abstract: There are a vast number of molecular interactions that occur at the cellular level. Among these molecular interactions, interactions between multiple proteins are a widely studied area of research due to the importance of these interactions in cellular function and their potential in drug development. PeSA is a desktop application developed to facilitate the in vitro peptide study analysis to predict protein-protein interactions. PeSA can effortlessly generate visual outputs like motifs, bar charts, and visual matrices. Our implementation of PeSA version 2.0 includes additional tools, including the ability to further score peptide lists for consensus amongst interactions. The software is also able to design de novo peptides based on sequence motifs (sequence generator), which can be used to help design additional experiments for motif validation. Further, the efficacy of the sequence generator was validated using the lysine methyltransferase, SETD8, to identify new substrates of methylation based on motif-based predictions developed using PeSA2.0. Graphical Abstract: ga1 Highlights: Position-specific scoring matrices are widely used to show biological interactions. PeSA2.0 generates positive and negative motifs to present analysis results. Peptide lists and proteins can be scored by similarity to PeSA2.0 generated motifs. PeSA2.0 can be used to design new studies by generating peptide sequences. PeSA2.0 provides real-time visual outputs to ease array analysis.